(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
It is observed that the decline of the empire will be attended by a profile of criminality. That profile may be extrapolated from the causes and conditions of impending collapse. In the case of the US empire, certain expressive and instrumental crime are expected to be observed. In its foreign policy, the US has stood up and sought to withdraw support from rogue proxies and their terrorist violence. This has produced a blowback of delegitimacy and disorder. Domestically, there are crimes associated with the unease of a failing ideological and economic enterprise, including hate crimes and accelerationist violence associated with ethno-nationalistic and settler colonial prejudices. Elites in a failing empire become more insular and besieged, demanding a less democratic and liberal environment for speech and political assembly, thus producing new categories of political crime.